ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI BIAYA PERBAIKAN DAN PEMELIHARAAN KAPAL STUDI PADA KAPAL-KAPAL PENYEBERANGAN (RO-RO) MILIK PT ASDP INDONESIA FERRY (PERSERO) - , Dani Andrian, S.E., Dr. Budi Harjanto Adv., DEM, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Shipping is one of the worldâs most capital- intensive industries due to the high cost of purchasing a ship. Therefore, many shipping company in Indonesia decide to invest in second- hand ship in order to minimize their investment cost. In the long term, the operational cost of second- hand ships will be higher than the new one, these costs include the repair and maintenance cost. Repair and maintenance cost is need to be allocated by ships owner to ensure that the ship will always be in the good condition during the economic lifetime of the ship. This research aims to identify the determinant of expenditure in ship repair and maintenance cost. Age, size and mileage as a proxy of utilization will be tested as the independent variable of repair and maintenance cost determinant. 33 ro-ro ships will be the sample of this research, where all of those ships are owned by PT ASDP Indonesia Ferry (Persero). The result of this research shows that age, size and mileage have positive and significant effect on ship repair and maintenance cost. All independent variables can exp lain the 46,88 percent of ship and maintenance cost.